1994
DOI: 10.1111/j.1476-5381.1994.tb14787.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of nitric oxide by angiotensin‐(1–7) from porcine coronary endothelium: implications for a novel angiotensin receptor

Abstract: The angiotensin I (AI) metabolite, A(1-7), elicited a concentration-dependent dilator response (ED50 > or = 2 microM) in porcine coronary artery rings which was markedly attenuated by the nitric oxide (NO) synthase inhibitor, NG-nitro-L-arginine, and abolished after removal of the endothelium. This effect of the heptapeptide was not mimicked by AII, AIII or A(3-8) at comparable concentrations. The A(1-7)-induced relaxation was not affected by AT1 or AT2 receptor blockade or cyclo-oxygenase inhibition, but was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
134
2
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(153 citation statements)
references
References 8 publications
13
134
2
4
Order By: Relevance
“…The present study adds to growing evidence that suggests the involvement of Ang-(1-7) receptors in cardiac regulation both in normal (Gironacci et al, 1994;Porsti et al, 1994;Brosnihan et al, 1996) or pathological conditions (Ferreira et al, 2001;Loot et al, 2002;Zisman et al, 2003). In addition, our results suggest that losartan might interfere with Ang-(1-7) receptors in the regulation of cardiac chronotropism, which probably accounts for the orthostatic hypotension observed in losartan, but not in candesartan, treated rats.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The present study adds to growing evidence that suggests the involvement of Ang-(1-7) receptors in cardiac regulation both in normal (Gironacci et al, 1994;Porsti et al, 1994;Brosnihan et al, 1996) or pathological conditions (Ferreira et al, 2001;Loot et al, 2002;Zisman et al, 2003). In addition, our results suggest that losartan might interfere with Ang-(1-7) receptors in the regulation of cardiac chronotropism, which probably accounts for the orthostatic hypotension observed in losartan, but not in candesartan, treated rats.…”
Section: Discussionsupporting
confidence: 72%
“…Taken together, the results of the present and previous studies (Ferreira et al, 2001;Collister & Hendel, 2003) suggest that losartan might be interfering in a chronotropic regulatory action mediated by Ang-(1-7) receptors. In this regard, there is pharmacological evidence for the presence of a selective Ang-(1-7) receptor in the heart (Ferreira et al, 2001) and coronary arteries (Porsti et al, 1994). In addition, immunoreactivity for Ang-(1-7) was recently detected in cardiac myocites (Averill et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Arterial splanchnic vasodilation was consistently detected in human cirrhosis [8,19] . A large number of studies have demonstrated the vasodilatory effect of Ang-(1-7) [20][21][22][23] . Possible mechanisms for this effect include bradykinin potentiation [21,22] , enhanced prostacyclin (PGI2) release from vascular smooth muscle cells [23] and direct stimulation of nitric oxide (NO) synthesis [20,22] .…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have demonstrated the vasodilatory effect of Ang-(1-7) [20][21][22][23] . Possible mechanisms for this effect include bradykinin potentiation [21,22] , enhanced prostacyclin (PGI2) release from vascular smooth muscle cells [23] and direct stimulation of nitric oxide (NO) synthesis [20,22] . NO, PGI2, carbon monoxide, endocannabinoids and other vasodilators have been associated with arterial splanchnic vasodilation [24] .…”
Section: Discussionmentioning
confidence: 99%
“…It was later shown that Ang-(1-7) produced endothelium-dependent dilation of the coronary arteries of pigs and dogs, which was mediated by NO and bradykinin (Porsti et al 1994;Brosnihan et al 1996). This response was independent of AT 1 or AT 2 receptors, or prostaglandins; however, ACE inhibition magnified the vasodilatory response of Ang-(1-7).…”
Section: Vascular Effects Of Ang-(1-7)mentioning
confidence: 99%